2017
DOI: 10.1016/j.jaci.2016.12.156
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Adjuvanted and Standard Sublingual Immunotherapy on Respiratory Function in Pure Rhinitis Due to House Dust Mite over a 5-Year Period

Abstract: Background: Allergen-specific immunotherapy (AIT) still remains the only causal treatment for IgE mediated respiratory diseases (rhinitis/asthma) In addition to the observed clinical decrease in symptoms, AIT can provide a long-lasting and preventive effect. In particular it can modify the progression from rhinitis to asthma. Methods: The study was observational, open, non randomized, controlled, prospective and performed in a real-life setting. Patients with pure mite-induced allergic rhinitis were followed-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Aside from allergen avoidance for the prevention of asthma and atopy, targeting allergic sensitization through immunotherapy, has been studied in the prevention of asthma and atopy in several controlled trials (Table 2). 9,12,13,15,16,47 The role of immunotherapy in prevention of new sensitization as well as in mitigation of asthma symptoms has been appreciated since the 1960s. 48 Immunotherapy can improve the likelihood that a known asthmatic will outgrow his asthma.…”
Section: Allergen Immunotherapymentioning
confidence: 99%
See 3 more Smart Citations
“…Aside from allergen avoidance for the prevention of asthma and atopy, targeting allergic sensitization through immunotherapy, has been studied in the prevention of asthma and atopy in several controlled trials (Table 2). 9,12,13,15,16,47 The role of immunotherapy in prevention of new sensitization as well as in mitigation of asthma symptoms has been appreciated since the 1960s. 48 Immunotherapy can improve the likelihood that a known asthmatic will outgrow his asthma.…”
Section: Allergen Immunotherapymentioning
confidence: 99%
“…9 Sublingual immunotherapy (SLIT) has been extensively studied for asthma and atopy prevention. 12,13,15,16 In one prospective, randomized controlled, proof of concept study in infants at high risk of atopy, the intervention group was treated with HDM oral immunotherapy, twice daily for one year, while the control was treated with placebo. While the study confirmed decreased sensitization to common allergens in the intervention group, there was no effect on the development of AD, food allergy, or wheeze.…”
Section: Allergen Immunotherapymentioning
confidence: 99%
See 2 more Smart Citations